Enhancing Chile's Fiscal Framework : Lessons from Domestic and International Experience. (International Monetary Fund, 2019)
This booklet summarizes the presentations in the conference titled 'Enhancing Chile's Fiscal Framework: Lessons from Domestic and International Experience,' organized by Chile's Ministry of Finance and the International Monetary Fund in January of 2019. The conference's objective was to explore challenges and possible opportunities to improve Chile's fiscal framework, including the fiscal rule, by looking at the Chilean and international experience. The conference had the valuable participation of current and former senior policymakers from Chile, including former Ministers of Finance ranging across the political spectrum and central bank presidents, which provided an insightful perspective in areas for improvement in the realm of fiscal policy. These views were complemented by representatives from the IMF and the Inter-American Development Bank, academics, and country officials from New Zealand and Peru, which provided lessons from the international experience.